EKSTERNALITAS POSITIF OBJEK WISATA (STUDI KASUS PANTAI LAMPUUK KABUPATEN ACEH BESAR) - Siti Shara Nurdin; Vivi Silvia (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This study aims to find out the positive externalities arising from the existence of Lampuuk beach attractions to the Lampuuk societies. Respondents in this study were traders directly affected by the Lampuuk beach attractions of 76 respondents and 4 village officials as support data. They are lampuuk societies also and feel the benefits of Lampuuk beach attractions. The method of analysis used is descriptive analysis. The results of the study showed that positive externalities were economic and social benefits. Economic benefits are opening up jobs that absorbed labor from the lampuuk resident, rise the incomes for the lampuuk societies, the four villages treasuries in lampuuk area and lampuuk area treasury, improve the welfare of the lampuuk societies, and increased the PAD of Aceh Besar district, while the social benefits is strengthened the good relationship inter-villages in lampuuk area. Keywords: Positive Externality, Economic Benefits, Social Benefits.